Founder and Organizer - Panayides, Angelos (My University, 2026)
CoFounded and co-chaired the Prototype Art & Design Conference, an academic and professional forum established in 2023 and held 3 editions to date. • Established and led an organising committee of 9 members, coordinating academic governance, planning, and delivery across all editions. • Served as Conference Co-Chair for all editions, overseeing academic quality, programme coherence, and professional standards. • Curated 12 conference talks and cross 3 editions, ensuring thematic alignment with contemporary research and practice in art, design, and multimedia. • Invited and coordinated 12 keynote speakers from France, Greece, Cyprus, UK, Spain, strengthening inter-institutional and interdisciplinary academic networks. • coordinated 4 workshops a practice-based workshops, supporting knowledge exchange between academia and professional practice. • Achieved formal institutional recognition of the conference as an obligatory component of the internship programme for Multimedia and Graphic Design students. • Directly contributed to the professional development of a considerable number of students per edition, integrating experiential learning, academic discourse, and industry engagement. • Managed a total conference budget of 3500€, ensuring transparent and effective allocation of resources across programming, logistics, and dissemination for the 3rd edition of the conference. • Oversaw all organisational operations, including scheduling, speaker coordination, workshop delivery, and evaluation. • Developed and produced printed and digital promotional materials distributed to various institutions and platforms. • Led social media and digital communication strategies, reaching 430 followers / 120 544 views in 90 days in the 3rd edition. • Attracted 90 total attendees, including participants from 12 institutions from local and international audiences. The Prototype Art & Design Conference has become a sustained institutional initiative, demonstrating leadership in academic service, curriculum integration, and disciplinary knowledge exchange at a local and international level.